Pengaruh Pengetahuan dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi: Peran Moderasi Keadilan Pajak dalam Perspektif Fikih Empat Mazhab - Khaerunnisanatun; Itah Miftahul Ulum; Agung Yulianto (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to examine the influence of tax knowledge and tax sanctions on individual taxpayer compliance, with tax fairness as a moderating variable. This study is also complemented by the perspective of the four schools of Islamic jurisprudence (fiqh) in viewing individual taxpayer compliance. The data used are primary data obtained through surveys using questionnaires administered to individual taxpayers at KPP Pratama Cirebon Satu. The research population comprised 151,206 taxpayers, with a sample size of 384 respondents determined using the Raosoft sample size calculator. The data analysis technique used is Partial Least Square (PLS) through the SmartPLS software. The results indicate that tax knowledge and tax sanctions affect individual taxpayer compliance, while tax fairness influences as a moderating variable. The perspective of the four schools of Islamic jurisprudence views taxpayer compliance towards state levies as Obligations that are in line with the principles of public interest and obedience as long as they do not conflict with Islamic law.